Magnetostriction Measurement of Giant Magnetoresistance Films on the Practical Substrates by using Inverse-magnetostriction Effect - Okita K. (EPJ Web of Conferences, 2013)
After forming electric devices, a magnetostriction effect sometimes deteriorates the sensitivity of sensors such as read heads of hard disk devices, or the bit stability of memories such as magnetic random access memories through the inverse-magnetostriction phenomenon. We should, therefore, know the magnetostriction constant of magnetic films on the practical substrates. In this paper, I present a new method by detecting the changes in coercive force, Hc, with mechanically bending the substrates. This method uses the inverse-magnetostriction effect and I show the magnetostriction constant can be calculated from the gradient of the applied stress vs. Hc curves. With this method, I have successfully measured the magnetostriction constant of the GMR films fabricated on the practical substrates with a high sensitivity over 10-7. This method will be useful for the magnetic thin films with a large anisotropy field.